Resonance Effect Decrease and Accuracy Increase of Piezoelectric Accelerometer Measurement by Appropriate Choice of Frequency Range - Zine Ghemari; Saad Salah; Rabah Bourenane (Shock and Vibration)
A suitable piezoelectric accelerometer mathematical model is proposed to extract a relationship of motion relative frequency as a function of natural frequency. This relationship helps to select appropriate accelerometer frequency range that minimizes measurement error and improves accuracy. It also allows deducing a formula relating the damping rate and the measurement error of the accelerometer. To protect the accelerometer from failure, the resonance phenomenon effect must be minimized. In order to achieve this objective, physical principle is modeled to find a precise relationship which can determine the accelerometer appropriate frequency range. The developed model was simulated and the obtained results have showed that the selection of the frequency range has minimized the measurement error, increased the accelerometer accuracy, and reduced the resonance effect. Finally a comparative study was conducted to show the importance of the obtained results compared to recent literatures.